Mukhabarah: Profit Loss Sharing Financing Scheme in Agricultural Land Management (Study in Tumpang District) - Santi Merlinda; Vidya Purnamasari; Ahmad Fawaiq Suwanan; Syahrul Munir (IAIN Syekh Nurjati Cirebon, 2021)
Schemes in the management of agricultural land are very diverse, ranging from self-management and cooperation through mukhabarah, muzara'ah contracts to rental systems. This paper aims to precisely determine the scheme of cooperation in the management of agricultural land in Tumpang District. The most frequently used of the several land management cooperation schemes is mukhabarah, which benefits both landowners and smallholders. The approach used is qualitative, with a case study method. The population in this study were all agricultural landowners in Tumpang District, and the sample used was landowners who used the mukhabarah scheme. Then, the instrument in this study was in-depth interviews conducted on smallholders and landowners. This study indicates that the mukhabarah scheme provides higher income to landowners compared to the rental system. Meanwhile, from the side of smallholders, the mukhabarah scheme provides and opens job opportunities and increases income from land management. Another trivial thing but becomes an important point is that landowners and sharecroppers can still share agricultural products with residents/neighbors through this scheme.